P14.100 Measurements of glioblastoma response to recurrence using spectroscopic measurements and MRI volumetry. (6th September 2019) - Chombar, J; Heintz, A; Constans, J
Abstract: BACKGROUND: Glioblastoma is the most aggressive and common primary malignant brain tumor in adults. The prognosis of patients with glioblastoma remains poor with a median life expectancy of 15 to 17 months and a survival rate of 5% at five years.Spectroscopy is becoming more and more used and the ratios studied allow in some cases a better prediction, at the recurrence, of the survival between certain ratios such as: Cho / Cr, NAA / Cr, Lac / Cr. Being able to combine all these ratios can allow us to obtain an additional survival index to take into account.This is why our study assesses whether MRS is coupled with volume, it is predictive of survival of the patient at 7 months. MATERIAL AND METHODS: Population: 30 Patients with glioblastoma treated with the STUPP protocol with and without bevacizumab at recurrence over a period of 36 months. Patients divided into three different groups depending on the type of resection (subtotal (20), partial (13), and biopsy (7)).MRI sequences every 2 months on MRI 3T and 1.5T. Sequences we used: diffusion, T2, T2 *, FLAIR, 3D FLAIR, 3D T1 with gadolinium injection; also monovoxel spectroscopy (TE at 35 and 144 ms, sometimes 288 ms). The volume variations (calculated by Aw.Server and ITK) are evaluated according to the RANO criteria.The MRS ratios (calculated by jMRUI) were clinically used are Cho / Cr (tumor proliferation), NAA / Cr (infiltration) and Lac / Cr (glycolytic metabolism). Longitudinal analyzes of volumes and ratios. RESULTS: 30 patients included in this study. The analysis of the results is that proliferation and / or glycolytic metabolism are more informative and predictive when there is absence of contrast enhancement, hyperperfusion or large volume variation. The global index (choline + lactate / NAA) could be a relevant criterion of judgment to better study the aggressiveness of the tumor and better predict the evolution of tumor volumes and survival. Intra-inter-operator differences on 2 segmentation software. CONCLUSION: The study shows us and confirms that the widest possible resection is to favor. Spectroscopy ratios vary earlier than the volumetry and give more information on the tumor processes and is sometimes predictive of survival.